Angola : 2021 Article IV Consultation and Six Review under the Extended Arrangement of the Extended Fund Facility and Request for a Waiver of Nonobservance of a Performance Criterion; Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2022)
Policies since 2018 have stabilized the economy in a very difficult environment. Yet many challenges remain for sustainable development, especially high debt and oil dependency. The authorities remain committed to continued reforms.